PENGARUH CORPORATE SOCIAL RESPONSIBILITY, KEPEMILIKAN MAYORITAS DAN CORPORATE GOVERNANCE TERHADAP AGRESIVITAS PAJAK (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2011-2014) - Dea Listika Sari; Edfan Darlis; Meilda Wiguna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to examine the influence of corporate social responsibility, majority ownership and corporate governance on tax aggressiveness. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange from 2011 to 2014. The number of samples are processed as many as 69 companies listed in Indonesia Stock Exchange from 2011-2014, so the amount of data processed is 276 data taken from four consecutive years of each company. Data analysis technique used is multiple regression analysis were processed with SPSS Windows 19. The results show that corporate social responsibility is the t (2.268)> t table (1.971) and significant (0.029) <(0.05), whose majority ownership t (-2.637)> t table (1.971) and significant (0.025) <(0.05), corporate governance t (-2.540)> t table (1.984) and significant (0.012) <(0.05) , Overall, it is known that corporate social responsibility, and corporate governance majority ownership has an effect on the aggressiveness of the tax of 69.8%. While 30.2% is influenced by other variables not examined in this study.Keywords : Responsibility, Ownership, Governance, Aggresiveness